Land Use Planning for Vegetable Farming in Benue State of Nigeria (Global Journal of Science Frontier Research, 2012)
Management of soil organic matter is the key to successful organic farming with regards to soil productivity. Vegetable production is most successful in soils rich in organic matter and also with adequate soil moisture. This paper examines two broad groups of soils in Benue State (the upland and the wetland soils) with respect to their suitability for organic vegetable farming. In 2008/2009 and 2009/2010 cropping seasons, a soil characterization study for field assessment of vegetable crop yields in the upland and wetland soils of Benue state was conducted. The wetland soils were found to be richer in organic carbon (2.28%) than the upland soils (0.87%). This singular difference had multiplier effects as wetland soils had higher total N (0.31%) and available P (9.8 mg kg-1), higher pH (6.7) and total exchangeable bases (12.8 mol kg-1) and by implication higher water holding capacity. Among the wetland soils, okra yields averaged 5.92mt ha-1 (wetland) as against 2.75 mt ha-1 (upland) and garden egg yields were 6.00mt ha-1 (wetland) and 4.50mt ha-1 (upland). These results indicated that wetland soils had greater advantage for organic farming than the upland soils. Since land use planning is all about allocation of land to optimize yields and minimize damage to soil resources, the wetland soils are therefore recommended for organic vegetable farming in Benue State.
Keywords: Land use planning; organic matter; organic vegetable farming